PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TIMED PAIR SHARE UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATA PELAJARAN IPS POKOK BAHASAN PASAR PADA SISWA KELAS VIII-B SMP NEGERI 1 ARJASA - Dyan Yuliana (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
The object of this research were 28 students on class VIII-B. The design of this study is Hopkins schema model with 4 phases, which are planning, action, observation, and reflection. Collecting research data, researcher uses observation method, interview, and test. Data analysis of this study uses qualitative descriptive analysis. The result of this study showed that student’s learning activities and their learning outcomes were increased. Student’s learning activity fulfill “middle active” category before doing an action. The result of learning activity analysis on the first cycle show percentage degree 78,57% and the daily test on the first cycle reach 78,57% classical mastery criterion. This showed that the application of Timed Pair Share learning model on the first cycle was not succeed yet, so this study was continued to the second cycle. The result of second cycle showed that student’s learning activity was on “active” category with percentage degree 86,11%. Besides that, daily test analysis on second cycle reached percentage degree 85,71%. Student’s achievement on daily test on second cycle showed that Timed Pair Share learning model affects student’s learning activity and their learning outcomes. It was proved based on the application of Timed Pair Share learning for students of class VIII-B State Junior High School 1 Arjasa fulfills classical mastery criterion.